miRNAs Related to Different Processes of Fracture Healing: An Integrative Overview - Groven, Rald V. M.; van Koll, Johan; Poeze, Martijn; Blokhuis, Taco J.; van Griensven, Martijn (Frontiers in Surgery, 2021)
Fracture healing is a complex, dynamic process that is directed by cellular communication and requires multiple cell types, such as osteoblasts, osteoclasts and immune cells. Physiological fracture healing can be divided into several phases that consist of different processes, such as angiogenesis, osteogenesis and bone resorption/remodelling. This is needed to guarantee proper bone regeneration after fracture. Communication and molecular regulation between different cell types and within cells is therefore key in successfully orchestrating these processes to ensure adequate bone healing. Among others, microRNAs (miRNAs) play an important role in cellular communication. microRNAs are small, non-coding RNA molecules of approximately 22 nucleotides long that can greatly influence gene expression by post-transcriptional regulation. Over the course of the past decade, more insights have been gained in the field of miRNAs and their role in cellular signalling in both inter- and intracellular pathways. The interplay between miRNAs and their mRNA targets, and the effect thereof on different processes and aspects within fracture healing, have shown to be interesting research topics with possible future diagnostic and therapeutic potential. Considering bone regeneration, research moreover focusses on specific microRNAs and their involvement in individual pathways. However, it is required to combine these data to gain more understanding on the effects of miRNAs in the dynamic process of fracture healing, and to enhance their translational application in research, as well as in the clinic. Therefore, this review aims to provide an integrative overview on miRNAs in fracture healing, related to several key aspects in the fracture healing cascade. A special focus will be put on hypoxia, angiogenesis, bone resorption, osteoclastogenesis, mineralization, osteogenesis, osteoblastogenesis, osteocytogenesis, and chondrogenesis.